Harnessing Electron Transfer from the Perchlorotriphenylmethide Anion to Y@C82(C2v) to Engineer an Endometallofullerene‐Based Salt. Issue 8 (28th March 2013) - Kareev, Ivan E.; Laukhina, Elena; Bubnov, Vyacheslav P.; Martynenko, Vyacheslav M.; Lloveras, Vega; Vidal‐Gancedo, José; Mas‐Torrent, Marta; Veciana, Jaume; Rovira, Concepció
Abstract We show that electron transfer from the perchlorotriphenylmethide anion (PTM−) to Y@C82(C2v) is an instantaneous process, suggesting potential applications for using PTM− to perform redox titrations of numerous endohedral metallofullerenes. The first representative of a Y@C82‐based salt containing the complex cation was prepared by treating Y@C82(C2v) with the [K+([18]crown‐6)]PTM− salt. The synthesis developed involves the use of the [K+([18]crown‐6)]PTM− salt as a provider of both a complex cation and an electron‐donating anion that is able to reduce Y@C82(C2v). For the first time, the molar absorption coefficients for neutral and anionic forms of the pure isomer of Y@C82(C2v) were determined in organic solvents with significantly different polarities.